2013
DOI: 10.9775/kvfd.2013.9008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Enterotoxigenic Gene Profiles of Bacillus cereus Strains Isolated from Dairy Desserts by Multiplex PCR

Abstract: The aim of this study was to investigate the presence of Bacillus cereus and to detect enterotoxigenic genes in dairy dessert samples utilising a multiplex PCR technique. A total of 100 samples, 25 keskul, 12 tavuk gogsu, 12 kazandibi, 30 supangle, 4 profiteroles and 17 sutlac were analysed. B. cereus contamination was found in 7 of 100 (7.0%) samples including 3 (25%) tavuk gogsu, 2 (6.6%) supangle, 1 (4%) keskul and 1 (5.8%) sutlac. The average number of B. cereus was between 2.0×10 1 -5.0×10 2 cfu/g in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…Lower incidences have been reported 60% ,55% , 48% ,35% and 15% from rice pudding samples by (32,27,16,30,17) respectively. lower mean value than our has been recorded 2.38×10 5 ±1.4×10 5 CFU/g by (16) .A much lower incidence 5.8% was revealed by (8).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Lower incidences have been reported 60% ,55% , 48% ,35% and 15% from rice pudding samples by (32,27,16,30,17) respectively. lower mean value than our has been recorded 2.38×10 5 ±1.4×10 5 CFU/g by (16) .A much lower incidence 5.8% was revealed by (8).…”
Section: Discussioncontrasting
confidence: 66%
“…Strict hygyienic measures should be applied in food production , insure clean sources for constituents, sufficient heat treatments when cooking , refrigeration as soon as possible to the products . 3.9 × 10 7 1.01× 10 4 74 % 37 50 Rice milk (rice pudding) 37.8 14 31 9 10 6 ≥10 7 10.8 4 0 0 10 7 ≥10 8 100 % 37 100 % 29 Total…”
Section: Results Represented Inmentioning
confidence: 99%
“…There are two types of severe foodborne diseases caused by B. cereus, the emetic (heat-stable) and the diarrheal type (heat-labile) [9][10][11][12] . The emetic and the diarrheal syndromes can occur when the bacterial cell concentration reaches a level of 10 5 to 10 8 CFU/g and 10 5 to 10 7 CFU/g, respectively [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…were positive ces gene responsible for emetic toxin production. Çadırcı, Gücüko glu, Terzi, Kevenk, and Mlişarlı (2013) while the ctyK1 gene was not identified in any sample. In the study conducted by Guinebretière and Broussolle (2002), from a total of 51 enterotoxigenic B. cereus strains, 49 were detected to have the nhe gene, 47 were found out to have the hbl gene and 17 were to have the cytK gene.…”
Section: Gel Electrophoresismentioning
confidence: 77%
“…Researchers also indicated that out of the 508 B. cereus isolates, 4.7% were positive ces gene responsible for emetic toxin production. Çadırcı, Gücükoğlu, Terzi, Kevenk, and Mlişarlı () reported that, amongst 20 isolates from seven positive samples obtained from 100 milk based dessert samples, 70% (14/20) had no hbl gene, 30% (6/20) had three enterotoxic HBL complex coding genes ( hblA, hblC, and hblD ), 40% (8/20) of the isolates contained three NHE complex coding genes ( nheA , nheB, and nheC ), 45% (9/20) contained two nhe genes ( nheA and nheB ) and 15% (3/20) contained one nhe gene (two NHEA and one NHEB ), while the ctyK1 gene was not identified in any sample. In the study conducted by Guinebretière and Broussolle (), from a total of 51 enterotoxigenic B. cereus strains, 49 were detected to have the nhe gene, 47 were found out to have the hbl gene and 17 were to have the cytK gene.…”
Section: Discussionmentioning
confidence: 99%